Injustice at home : [videorecording (DVD)] looking like the enemy (KSPS-TV, 2019)
During WWII, almost the entire population of Japanese Americans on the West Coast were forcibly removed from their homes and incarcerated. Their only crime was looking like the enemy. Of the 120,000 imprisoned, two-thirds were American citizens; many were women and children. It has been called "our worst wartime mistake." The KSPS Public Television documentary entitled, Injustice at Home: Looking Like the Enemy, focuses on the Japanese American community in Washington State during WWII, both inside and outside the evacuation zone; chronicling the struggles, experiences, and perseverance through discrimination, racism and injustice. -- Container.